Studi kasus: Penyakit FIP (feline infectious peritonitis) pada kucing domestik di UPTD Puskeswan Makassar - Kumala, Nur Hakiki Dewi; Muthiadin, Cut; Nurmayanti, Nurmayanti (Filogeni: Jurnal Mahasiswa Biologi, 2024)
Feline Infectious Peritonitis (FIP) is one of the infectious diseases in cats caused by the Feline Corona Virus (FCov). This disease can occur due to lack of knowledge regarding animal health, causing many health problems in cats. The purpose of this study was to determine the number of cats experiencing FIP cases, to find out how to diagnose the disease and to find out the prevention and treatment of FIP in cats. The research method used an interview method with a descriptive approach. The results of the study showed that there were 3 cases of FIP that attacked domestic cats with 2 types of FIP, namely wet FIP ​​(effusive) and dry FIP (non-effusive). Diagnosis of the disease is based on the clinical symptoms that appear, medical history, physical examination and ultrasound examination. Treatment actions that can be taken are in cases of wet FIP, removing fluid that accumulates in the cat's abdomen and giving vitamins/antibiotics to dry FIP sufferers. FIP disease is easily transmitted and fatal. Therefore, it can be prevented by maintaining and caring for cats properly and separating cats that have been infected with FIP from healthy cats.